2016
DOI: 10.1681/asn.2016070726
|View full text |Cite
|
Sign up to set email alerts
|

Renal Fanconi Syndrome and Hypophosphatemic Rickets in the Absence of Xenotropic and Polytropic Retroviral Receptor in the Nephron

Abstract: Tight control of extracellular and intracellular inorganic phosphate (Pi) levels is critical to most biochemical and physiologic processes. Urinary Pi is freely filtered at the kidney glomerulus and is reabsorbed in the renal tubule by the action of the apical sodium-dependent phosphate transporters, NaPi-IIa/NaPi-IIc/Pit2. However, the molecular identity of the protein(s) participating in the basolateral Pi efflux remains unknown. Evidence has suggested that xenotropic and polytropic retroviral receptor 1 (XP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
44
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 61 publications
(47 citation statements)
references
References 11 publications
1
44
1
Order By: Relevance
“…As examples in the kidney, Type II sodium-dependent phosphate cotransporters are regulated by dietary phosphate supply (Bourgeois et al, 2013), and gene expression of Trpv5 encoding a renal calcium transport protein is controlled by 1,25(OH) 2 -vitamin D 3 (Hoenderop et al, 2001). As examples in the bone, Fgf23 expression is stimulated by 1,25(OH) 2 -vitamin D 3 (Liu et al, 2006) or PTH (Kawata et al, 2007), while dietary phosphate restriction or renal phosphate-wasting disorders reduce Fgf23 expression (Vervloet et al, 2011, Schlingmann et al, 2016, Ansermet et al, 2017. Even intravenous calcium loading in rats increased Fgf23 expression in bone and hormone concentrations in the serum (Shikida et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…As examples in the kidney, Type II sodium-dependent phosphate cotransporters are regulated by dietary phosphate supply (Bourgeois et al, 2013), and gene expression of Trpv5 encoding a renal calcium transport protein is controlled by 1,25(OH) 2 -vitamin D 3 (Hoenderop et al, 2001). As examples in the bone, Fgf23 expression is stimulated by 1,25(OH) 2 -vitamin D 3 (Liu et al, 2006) or PTH (Kawata et al, 2007), while dietary phosphate restriction or renal phosphate-wasting disorders reduce Fgf23 expression (Vervloet et al, 2011, Schlingmann et al, 2016, Ansermet et al, 2017. Even intravenous calcium loading in rats increased Fgf23 expression in bone and hormone concentrations in the serum (Shikida et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…(23) Conditional inactivation of Xpr1 in renal tubules in mice will impair renal Pi reabsorption, which results in a reduced serum Pi level and bone mineralization. (34) Hence, in the Xpr1-deficient fetuses, although the abnormal placental Pi exchange might be a contributing factor, the XPR1 deficiency throughout all fetal tissues, especially in the kidneys and intestines, might be the main factor underlying the reduced Pi level in fetal serum and amniotic fluid and the reduction in fetal skeletal mineralization.…”
Section: Discussionmentioning
confidence: 99%
“…However, it has been reported that in zebrafish - xpr1b , an orthologue of XPR1, is crucial for the differentiation of tissue-resident macrophages and microglia 107 . In mice, the full knockout of Xpr1 is embryonic lethal 108 , but the embryonic phenotype has not been characterized. Thus, further studies are needed to dissect the role of PFBC genes in microglial function.…”
Section: Discussionmentioning
confidence: 99%